Assessment of corrosion-induced damage and its effect on the structural behavior of RC beamscontaining supplementary cementitious materials - Ahmed, Shaikh; Maalej, M; Paramasivam, P; Mihashi, H (John Wiley & Sons, 2006)
This paper reports the results of an experimental program on the effect of steel loss and corrosion induced-damage (cracking, delamination, spalling, etc.) on the post-corrosion flexural response of reinforced concrete beams incorporating supplementary cementing materials (fly ash, slag and silica fume) used as partial replacement of ordinary Portland cement. Eight reinforced concrete beams measuring 2.5 m in length and 210 300 mm in cross-section were cast, four of which were subjected to accelerated corrosion. Among all specimens incorporating supplementary cementing materials (SCM), the specimen containing fly ash showed the best performance in terms of the highest residual load carrying capacity at failure. Its best performance was also evident from the lowest measured steel loss, the least corrosion-induced cracking and the lowest tendency for the concrete cover to delaminate as measured by a concrete-embeddable fiber optic strain sensor (FOSS). Correlation between the amount of steel loss and the reductions in load carrying at failure was also established.